The Communicative Activities of Public Relations and Their Role in Security Awareness (The Counter-Terrorism Service as a Model) - Anfal Ghazi Al-Sarray, Asst. Lecturer; Ameer Ghazi Jassim, Asst. Lecturer (lark, 2026)
This study aims to examine the communicative activities of the Public Relations unit within the Iraqi Counter-Terrorism Service and their role in enhancing security awareness, focusing on how these activities are employed to build public trust and effectively convey security messages. The researcher utilized in-depth interviews as the primary datacollection tool, allowing a detailed understanding of the methods and communication strategies used within the agency. The results indicated that the Public Relations unit implements a variety of communicative activities, ranging from preventive and awareness-raising to corrective measures, using diverse media channels including national media, websites, and social media platforms, with continuous impact assessment. These activities significantly contributed to raising public security awareness, building trust with citizens, and reducing rumors and external recruitment attempts, despite technical and structural challenges faced by the agency. The study emphasizes the importance of strengthening the communicative capacities of public relations within security institutions, adopting innovative and flexible methods to engage with both internal and external audiences, ensuring accurate and effective delivery of security messages, and fostering an environment of transparency and mutual trust.